Local Conditions and Conditions Ethishtirilgan Soy Uroglaring Mechanical Physicist Specializing in Research, Masses and Geometric Nodes of the Chimney Aspirin Samaring Technique of all Types of Separation of Smokemalaring Energy Tejamcorder Constructionin (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article focused on preparing plant seeds for processing, improving existing devices that meet current demand, aspirating seeds by size and mass, and creating separating processes and devices, and creating devices that are less energy efficient.